Islam : a mosaic, not a monolith - Gregorian, Vartan (Brookings Institution Press, 2003)
For readers unfamiliar with the world's fastest-growing religion, Gregorian provides an accessible overview of its tenets, institutions, evolution, and historical role, along with insights into the current state of Muslim societies and the challenges they face.